YAYLOV YERLARIDAN FOYDALANISH BO‘YICHA XORIJIY TAJRIBALAR - Erkinova M.L (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract. This article analyzes the experience of leading countries in the use, management  and  evaluation  of  pasture  lands.  In  particular,  it  discusses  land  use practices, taxation systems, leasing policies, and modern monitoring technologies in countries such as the USA, China, Kazakhstan, Russia, Canada, and Australia. The article also addresses the application of NDVI and other vegetation indices in pasture monitoring.